Enrichment of drinking water with Ca and Mg by a fluidized bed recarbonization reactor: a case study of Devičie, Slovak Republic. (4th April 2022) - Rapant, Stanislav; Cvečková, Veronika; Čermák, Patrik
Abstract: A low content of Ca and Mg in drinking water causes increased health risks. To increase the Ca and Mg contents in the drinking water supplied to the inhabitants of the village of Devičie, a prototype of a fluidized bed recarbonization reactor (RRF) was proposed and tested. A half-burnt dolomite (HBD) was used for the recarbonization. In the RRF, the HBD is kept in buoyancy with the help of water circulation. The capacity of the circulation pump is up to 5 m 3 h −1 and the volume of discharged concentrate, which is added directly to the water source, is up to 0.2 m 3 h −1 . The volume of water circulated between the reactor and the circulating tank is many times higher than the volume of discharged water. In 24 h, the Ca and Mg contents stabilized at an equilibrium value of 80 mg L −1 for Ca and 120 mg L −1 for Mg, which corresponded to the equilibrium of formation and removal of ions from the system. The concentrate was diluted with the water in the reservoir at a ratio of 1:10, and it achieved the desired increase in Mg and Ca contents by more than 10 and 6 mg L −1, respectively. HIGHLIGHTS: Increasing the Ca and Mg contents in soft drinking water is beneficial for human health. The prototype of the developed recarbonization reactor produces a concentrate with high Ca and Mg contents. The efficiency of the reactor is conditioned mainly by repeated washing of the carbonate rock. Graphical Abstract